Filogenia molecular dos xenarthra (Mammalia): análise do grupo cingulata a partir de sequências nucleotídicas do gene mitocondrial rRNA 16S - PAMPLONA NETO, Christóvam (Universidade Federal do Pará, 2013)
Xenarthra is the group of mammals which include armadillos, anteaters and sloths. South America was the landscape of their natural history. Only toward the end of the Cenozoic they spread from South America to Cen-tral America and, in decreasing variety, farther in North America and to some of the West Indian islands. The 31 extant species are described within xenarthran lineage. They are distributed in 13 genera, four families (Brady-podidae, Magelonychidae, Myrmecophagidae and Dasypodidae) and two or-ders orders (Cingulata and Pilosa). The phylogeny of this group has been addressed by multiple researchers using both morphological and molecular data sets. Through phylogenetic analyses of protein-coding nuclear genes and mitochondrial genes, Delsuc et al. (2003) found evidence for the hy-pothesis of monophyly of the subfamilies Dasypodinae, Tolypeutinae and Euphactinae within the family Dasypodidae. They had generated the fol-lowing tree: (((Bradypus, Choloepus)100, ((Myrmecophaga, Tamandua)100, Cyclopes)100), ((D. kappleri, D. novemcinctus)100, (Tolypeutes, (Priodontes, Cabassous)54)100, (Zaedyus, (Euphractus, Chaetophractus)60)100)). Gaudin (2005) presented a work that reviewed and extended the morphological data available, concluding that the extant armadillos are divided in two groups, a basal group (Dasypodinae) and another more derivative (Euphractinae), in accordance with the following arrangement: (Bradypus, Tamandua), (Dasy-pus, (Priodontes, (Cabassous, (Tolypeutes, (Euphractus, Chaetophractus, (Za-edyus, Ch/amyphorus)42)36)72)72)40)85). In the work described in this dis-sertation, we sequenced part of the 16S rRNA mitochondrial gene from 12 extant taxa of Xenarthra to perform phylogeny analysis based on maximum-likelihood. Our results are presented analysing the 16S gene data alone, an concatenated with the dataset of Delsuc et al. (2003): (Bradypus, (Choloe-pus, ((Cyclopes, (Myrmecophaga, Tamandua)100)100, (Dasypus, (((Cabas-sous, Priodontes)68, Tolypeutes)100,((Chaetophractus, Euphractus)65, Za-edyus)100)100)100)100)100). Results were similar to those of previous stu-dies. However, an improvement in bootstrap values of certain branches could be noticed. We believe that Transposable Elements (UNES) are the molecular markers more adjusted to confirm uncertain arrangements sugges-ted by phylogenetic analyses mitocondrials and nuclear genes.